microRNA-193a-5p Suppresses the Migratory Ability of Human KATO III Gastric Cancer Cells through Inhibition of Vimentin and MMP-9 - Amir Baghbanzadeh; Elham Baghbani; Khalil Hajiasgharzadeh; Saeed Noorolyai; Vahid Khaze; Behzad Mansoori; Masoud Shirmohamadi; Behzad Baradaran; Ahad Mokhtarzadeh (Tabriz University of Medical Sciences, 2022)
Purpose: microRNA-193a-5p is one of the well-known tumor suppressor miRNAs in the body but in many cases, its expression became reduced in patients suffering from gastric cancer (GC). The main purpose of this study was to restore the function of this miRNA in human GC cells and investigating the effects of enhanced expression of miR-193a-5p on proliferation, apoptosis, and migration of GC cells upon in vitro transfection. Methods: The KATO III gastric cancer cells were treated with 100 nM of miR-193a-5p or negative control sequences. Following that, the MTT assay, flow cytometry assay, and wound-healing assay were applied to estimate the impacts of enhanced expression of this miRNA on the viability, apoptosis, and migration rate of the cells, respectively. Moreover, the total RNA was isolated and alterations in the mRNA expression ratio of migratory genes were measured by qRT-PCR techniques. Results: The findings designated that enhanced expression of miR-193a-5p suppressed the migratory ability of the cells, but had no significant effects on cell survival or apoptosis of the transfected cells. In addition, this inhibitory function of miR-193a-5p on the migration rate of the KATO III cell line occurs with concurrent suppression of vimentin and MMP-9 gene expression. Conclusion: It can be concluded that miR-193a-5p negatively influences the migratory ability of the cancerous cells and restoring its effects can be regarded as a promising target of future therapeutic interventions, especially for GC metastasis.